2010
DOI: 10.1053/j.gastro.2010.05.074
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Nicotinamide Adenine Dinucleotide Phosphate Oxidase 2 Plays a Key Role in Stellate Cell Activation and Liver Fibrogenesis In Vivo

Abstract: BACKGROUND & AIMS-Hepatocyte apoptosis and activation of hepatic stellate cells (HSC) are critical events in fibrogenesis. We previously demonstrated that phagocytosis of apoptotic hepatocytes by HSC is profibrogenic. Based on this, as well as the observation that NADPH oxidase induction is central to fibrogenesis, our aim was to study the phagocytic NADPH oxidase, NOX2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
126
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(128 citation statements)
references
References 34 publications
1
126
0
1
Order By: Relevance
“…Ongoing hepatocyte apoptosis or necroptosis, as occurs predominantly in liver diseases characterized by enhanced oxidative and endoplasmic reticulum stress, lysosomal activation, and mitochondrial damage (ASH, NASH), is a strong trigger of fibrogenesis (16,50). Phagocytosis of apoptotic hepatocytes by myofibroblasts triggers their fibrogenic activation via NADPH oxidase 2 (NOX2) (51) and the JAK/STAT and PI3K/ Akt pathways (52). Notably, inhibition of hepatocyte apoptosis by a pan-caspase inhibitor or an antagonist of cathepsin B (a lysosomal trigger of apoptosis) ameliorated (biliary) fibrosis in mice…”
Section: Figurementioning
confidence: 99%
“…Ongoing hepatocyte apoptosis or necroptosis, as occurs predominantly in liver diseases characterized by enhanced oxidative and endoplasmic reticulum stress, lysosomal activation, and mitochondrial damage (ASH, NASH), is a strong trigger of fibrogenesis (16,50). Phagocytosis of apoptotic hepatocytes by myofibroblasts triggers their fibrogenic activation via NADPH oxidase 2 (NOX2) (51) and the JAK/STAT and PI3K/ Akt pathways (52). Notably, inhibition of hepatocyte apoptosis by a pan-caspase inhibitor or an antagonist of cathepsin B (a lysosomal trigger of apoptosis) ameliorated (biliary) fibrosis in mice…”
Section: Figurementioning
confidence: 99%
“…A role for the NADPH oxidases in chronic liver diseases, such as fibrosis and viral hepatitis, related to chronic inflammation, has been proposed (9,10). In the pathogenesis of alcoholic liver steatosis, there is an increase in NADPH oxidase activity and predominance of pro-oxidant agents, exceeding the capacity of the organic antioxidant defense (8).…”
Section: Introductionmentioning
confidence: 99%
“…The results are consistent with previous studies reporting that TGF-b increased ROS production in numerous types of nonphagocytic cells, including aortic smooth muscle cells; prostatic stromal cells; hepatic stellate cells; and cardiac, lung, and skin fibroblasts (Hecker et al, 2009;Bocchino et al, 2010;Bondi et al, 2010;Michaeloudes et al, 2011;Sampson et al, 2011;Baek et al, 2012). It has been shown that TGF-b increases the activity of NAD(P)H oxidase and the expression of Nox2 and Nox4, and that both of these two homologs of the Nox family are the ones that mainly mediate the TGFb-induced ROS accumulation (Hecker et al, 2009;Jiang et al, 2010;Crestani et al, 2011;Sampson et al, 2011). Here we also found that the mRNA and protein expression levels of Nox4 were up-regulated in corneal fibroblasts treated with TGF-b, suggesting that TGF-b may be involved in the myofibroblast differentiation of corneal fibroblasts via a pathway involving Nox4-mediated ROS generation.…”
Section: Discussionmentioning
confidence: 99%